Development of model schools and practices for minimizing violence among students - Kantita Sripa; Theeravut Ninphet; Phonraphee Thummaphan; Sorat Glubwila (International Journal of Adolescence and Youth)
Violence among students in Thai society is a growing concern. This study aimed to develop model schools to address violence, evaluate their effectiveness, and propose a scalable practice model. Nine vocational schools in Bangkok implemented a participatory action research (PAR) approach using the PAOR cycle. Surveys, focus groups, and observations collected data, which underwent qualitative and quantitative analysis. Results showed that, compared to the previous year, two schools had no violent incidents, two saw a 50% reduction, and five achieved a 100% reduction in violence. Qualitative findings indicated improvements in student behavior, management systems, and collaboration networks. Key success factors included personnel commitment, strong networks, and adaptable management. The study created the ‘3S3C Practice Model,’ which integrates core activities with ‘T.E.A.M. Principles’ to enhance implementation. This model offers a framework for reducing student violence. Future research should focus on validating its applicability and scalability in diverse educational settings.